Laboratory evaluation of biosolids stabilized with demolition wastes as an embankment fill material - A. Arulrajah; F. Maghool; S. Horpibulsuk; M. W. Bo; L. Shen (Lowland Technology International, 2018)
Biosolids (Bio) are air-dried sewage sludge from wastewater treatment plants.Stockpiles of Bioare rapidly increasing around the globe. The primary aim of this paper was to evaluate the potential for Bio stabilized with demolition wastes as an embankment fill material. This laboratory evaluation study was undertaken to evaluate the geotechnicalproperties of Biowhen stabilized with various percentages of demolition wastes, being Crushed Brick (CB) and Crushed Concrete (CC). The standard compaction results indicated that the dry density of Bio increased with the addition of both demolition wastes. The optimum moisture content of Bio was found to consistently decrease with increasing amounts of demolition wastes. The gradation, pH value and specific gravity of Bio samples improved with the addition of demolition wastes. The California Bearing Ratio (CBR) value of Bio samples was increased with the addition of CB and CC, with the optimum value found to be achieved with 50% CC content (Bio50/CC50). The positive outcomes of this research project will potentially enable Bio to be used in combination with demolition wastes in embankment fill applications. This sustainable approach will reduce the demand for virgin materials and will potentially divert significant quantities ofthese waste materials fromlandfills and into a high value embankment fill material.